Reign in the membrane: How common lipids govern mitochondrial function. (April 2020) - Funai, Katsuhiko; Summers, Scott A.; Rutter, Jared
Abstract: The lipids that make up biological membranes tend to be the forgotten molecules of cell biology. The paucity of data on these important entities likely reflects the difficulties of studying and understanding their biological roles, rather than revealing a lack of importance. Indeed, the lipid composition of biological membranes has a profound impact on a diverse array of cellular processes. The focus of this review is on the effects of different lipid classes on the function of mitochondria, particularly bioenergetics, in health and disease.